2005
DOI: 10.3354/ame040283
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactivation in two freshwater ciliates: differential responses to variations in UV-B flux and temperature

Abstract: The effects of UV-B radiation on 2 ciliate species (Glaucoma sp. and Cyclidium sp.) from a clear oligotrophic lake were examined under laboratory conditions with and without photoreactivating radiation (PRR: UV-A and visible light). Glaucoma sp. was exposed to 3 UV-B intensities at 4 temperatures to simulate a range of environmentally relevant conditions. Population growth of Glaucoma sp. declined with increasing levels of UV-B exposure in treatments receiving PRR; blocking PRR generally resulted in 100% morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…Only the activity of the antioxidant enzyme catalase has been shown not to be thermally sensitive in response to UVR exposure in L. peronii tadpoles [72]. However, the DNA repair mechanisms of enzymatic photoreactivation (EPR) and nucleotide excision repair (NER) have been shown to increase with increasing temperature in ciliates [115], freshwater crustaceans [116], marine macroalgae [117], tobacco cells [118] and echinoid embryos [119], however, Connelly et al [120] found the opposite to be true in Daphnia. The photoprotective mechanism of ROS reduction by enzymatic antioxidant activity has also been found to be thermally sensitive in summer-caught mosquito fish Gambusia holbrooki exposed to UVR [39].…”
Section: Uvr and Abiotic Factors Temperaturementioning
confidence: 99%
“…Only the activity of the antioxidant enzyme catalase has been shown not to be thermally sensitive in response to UVR exposure in L. peronii tadpoles [72]. However, the DNA repair mechanisms of enzymatic photoreactivation (EPR) and nucleotide excision repair (NER) have been shown to increase with increasing temperature in ciliates [115], freshwater crustaceans [116], marine macroalgae [117], tobacco cells [118] and echinoid embryos [119], however, Connelly et al [120] found the opposite to be true in Daphnia. The photoprotective mechanism of ROS reduction by enzymatic antioxidant activity has also been found to be thermally sensitive in summer-caught mosquito fish Gambusia holbrooki exposed to UVR [39].…”
Section: Uvr and Abiotic Factors Temperaturementioning
confidence: 99%
“…This implies little role for NER in Paraphysomonas, and a dominant role of PER, which is consistent with observations of some other heterotrophic protists, including the ciliates Paramecium tetraurelia and Glaucoma sp. (26,31). P. tetraurelia had greater clonal longevity if it received PRR when exposed to UV-B, while populations of Glaucoma sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, PER is not ubiquitous in heterotrophic protists and can vary even within the same genus. One strain of the ciliate Cyclidium was found to have very little tolerance of UV-B, whether PRR was present during UV-B exposure or not (26), while another clone did not accumulate any measurable DNA damage when exposed to UV-B with PRR (33). NER is a metabolically costly and relatively slow DNA repair mechanism compared to PER (30,35), and it may be that the rapid population growth of protists selects for PER over NER.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations